2007
DOI: 10.1111/j.1469-7610.2007.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Family context and young children's responses to earthquake

Abstract: These findings demonstrate that young children's responses to an abrupt, negative environmental event, such as an earthquake, are influenced in part by the nature of the parent-child relationship prior to the event as well as by the responses parents exhibit following the event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 30 publications
(36 reference statements)
1
52
0
Order By: Relevance
“…Second, parent-child relationships influence children's responses to traumatic events (Fremont, 2004;Osofsky, 1999;Gustafsson, Larsson, Nelson, & Gustafsson, 2009b. Power, 2004Proctor et al, 2007), and adverse family circumstances that unfavorably affect the parents' ability to support their child in the face of such exposures can be an important determinant for the outcome. In a review (Grant et al, 2006) on moderating and mediating effects of stressors on child and adolescent psychopathology the authors conclude that there was substantial evidence for the mediating role of family relationship in the relationship between stressors in general and child and adolescent psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Second, parent-child relationships influence children's responses to traumatic events (Fremont, 2004;Osofsky, 1999;Gustafsson, Larsson, Nelson, & Gustafsson, 2009b. Power, 2004Proctor et al, 2007), and adverse family circumstances that unfavorably affect the parents' ability to support their child in the face of such exposures can be an important determinant for the outcome. In a review (Grant et al, 2006) on moderating and mediating effects of stressors on child and adolescent psychopathology the authors conclude that there was substantial evidence for the mediating role of family relationship in the relationship between stressors in general and child and adolescent psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions related to the new traumatic event should consider how pre-existing family context may impact children's reactions to an external trauma, and parents' abilities to be supportive following the new stressor (Proctor, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the earlier studies have indicated that natural disaster stress affects parental psychological health and family function and that this correlates with the children's mental health [17,18]. One study found that child abuse reports were disproportionately higher after the occurrence of a natural disaster [19].…”
Section: Introductionmentioning
confidence: 99%